Management of Large Proximal Ureteral Calculi: A Three-year Multicenter Experience of Simultaneous Supine Percutaneous Nephrolithotomy and Retrograde Ureterolithotripsy - Chen, Yu-Chen; Chen, Hao-Wei; Juan, Yung-Shun; Lo, Ing-Shiang; Shih, Ming-Chen Paul; Wu, Wen-Jeng; Jhan, Jhen-Hao; Huang, Tsung-Yi (Urology Journal, 2019)
Purpose: To share our multicenter experience using a safe and effective method for treating large proximal ureteral calculus by simultaneous supine percutaneous nephrolithotomy (sPCNL) and retrograde ureterolithotripsy (URSL) in the Galdakao-modified supine Valdivia position. Materials and Methods: Between December 2014 and August 2017, all patients with large proximal ureteral stones (> 15 mm) who underwent simultaneous sPCNL and retrograde URSL at three medical centers were retrospectively reported. The ureter stone was pushed back (retrograde) with the ureteroscope and was retrieved using forceps with a nephroscope through an Amplatz sheath. Surgical methods and outcomes were described to improve our experience and management of large proximal ureteral calculi. Results: A total of 31 patients underwent simultaneous sPCNL and retrograde URSL. The mean patient age, stone size, operating time, and postoperative hospital stay were 57 years (range, 32–74 years), 20.1 mm (range, 15.0–37.9 mm), 81 minutes (range, 30–150), and 3.2 days (range, 2–7 days), respectively. There were 10 modified Clavien grade I and five grade II complications. No blood transfusions were necessary in this series. All patients were treated with double-J stents without a nephrostomy tube. Only one patient did not achieve stone-free status because of the strict stone impaction into the ureteral wall. This patient received auxiliary URSL after two months. Thereafter, the overall stone-clearance rate at three months was 100%. Conclusion: Our preliminary data showed that this modified method is safe and effective for treating large proximal ureteral stones.